Computer-Aided Design of Elliptically Focused Bootlace Lens for Multiple Beams - G. S. Tomar (International Journal of Antennas and Propagation)
The design of elliptically focused microwave bootlace lens is investigated and improved design is proposed. The proposed design of the lens is capable of scanning wide area and is compact in size than the other available designs. The phase error is calculated and compared with conventional design of bootlace lens. The results are obtained using Matlab coding and are in accordance to the theoretical values. This design is intended to be used in next generation cellular mobile communication with tilt of required angle at base stations and also it can be used as multiple beam-forming networks for avoiding deafness problem in the ad hoc networks with greater efficiency and saving radiated power.